2016
DOI: 10.1103/physreve.94.032306
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid dynamics in delay-coupled swarms with mothership networks

Abstract: Swarming behavior continues to be a subject of immense interest because of its centrality in many naturally occurring systems in physics and biology, as well as its importance in applications such as robotics. Here we examine the effects on swarm pattern formation from delayed communication and topological heterogeneity, and in particular, the inclusion of a relatively small number of highly connected nodes, or "motherships", in a swarm's communication network. We find generalized forms of basic patterns for n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For example, an individual agent of a flock can be slow enough to respond to a signal coming from its neighbour. This causes communication-delay [38,39,40,41]. It has been shown that in presence of a noise induced transition from translatory to rotatory motion of agents [42], the time-delayed communication among them can introduce further instabilities where the harmonically interacting agents can form dynamic clusters or swarms, with a high degree of polarity [38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an individual agent of a flock can be slow enough to respond to a signal coming from its neighbour. This causes communication-delay [38,39,40,41]. It has been shown that in presence of a noise induced transition from translatory to rotatory motion of agents [42], the time-delayed communication among them can introduce further instabilities where the harmonically interacting agents can form dynamic clusters or swarms, with a high degree of polarity [38].…”
Section: Introductionmentioning
confidence: 99%
“…Since the latter class of models derive from basic physical principles, they showcase a broader spectrum of emergent motion patterns, and they can more easily incorporate, e.g., active-matter dynamics 15,43 and collective motion on arbitrary surfaces 46 . Recent work has begun to address network structure in such physically-inspired swarming systems, including how topology affects robustness to noise 47 and how heterogenous topology drives the formation of hybrid motion states 48 . Yet, much remains unknown about how complex topology influences the dynamical stability of swarms with general nonlinear interactions and under what circumstances a sparse swarming network can maintain coherent motion of all its agents-especially in the much broader range of collective-motion patterns without rigid velocity consensus.…”
Section: Introductionmentioning
confidence: 99%
“…To make progress, we consider a generic system of mobile agents moving under the influence of self-propulsion, friction, and pairwise interaction forces 41,43,47,49 mediated through a network 42,48 . In the absence of interactions, each swarmer will tend to a fixed speed, which balances its self-propulsion and friction but has no preferred direction 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the latter class of models derive from basic physical principles, they showcase a broader spectrum of emergent motion patterns, and can more easily incorporate, e.g., active-matter dynamics 15 , 43 and collective motion on arbitrary surfaces 47 . Recent work has begun to address network structure in such physically-inspired swarming systems, including how topology affects robustness to noise 48 and how heterogenous topology drives the formation of hybrid motion states 49 . Yet, much remains unknown about how complex topology influences the dynamical stability of swarms with general nonlinear interactions and under what circumstances a sparse swarming network can maintain coherent motion of all its agents—especially in the much broader range of collective-motion patterns without rigid velocity consensus.…”
Section: Introductionmentioning
confidence: 99%
“…To make progress, we consider a well known physics-based model of mobile agents moving under the influence of self-propulsion, damping, and pairwise interaction forces 41 , 43 , 48 , 50 , to which we add explicit sparse networks that mediate and constrain the inter-agent interactions 42 , 49 . In the absence of interactions, each swarmer will tend to a fixed speed, which balances its self-propulsion and damping but has no preferred direction 47 .…”
Section: Introductionmentioning
confidence: 99%